PENGARUH PENGGUNAAN BAHAN PENGISI (FILLER) TEPUNG KELADI (Colocasia esculenta) PADA PEMBUATAN NUGGET AYAM TERHADAP UJI ORGANOLEPTIK - Suartini Suartini; A. Tenny Damayanti Indriastuti; Heny V Saiya (Musamus Journal of Livestock Science, 2018)
The objective of this study was to the effect as filler of chicken nugget on organoleptik or hedonik test. This research was conducted in the laboratory of animal sains in MusamusUniversity, Merauke. This study used a Randomized Complete Design Method (RAL) by using the 3 treatments and 3 replicates. The treatment combit A1 (10,5% wheat flour : 4,5% taro flour), A2 (7,5% wheat flour : 7,5% taro flour), A3 (4,5% wheat flour : 10,5% taro flour). The parameters were observed in this study consists colour, aroma, texture, flavour. The result showed that treatment A1 more preferable onflavour and texture.